PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI (KAHOOT) TERHADAP HASIL BELAJAR SISWA KELAS XI DI SMAI AL-MAARIF SINGOSARI MALANG - Syafiyatul Mafruhah; Ika Ratih Sulistiani; Fita Mustafida (VICRATINA, 2019)
This study aims to find out the use of application-based interactive learning media (kahoot), find out student learning outcomes after using application-based learning media (kahoot) and find out whether there is an effect of using application-based learning media (kahoot) on learning outcomes of class XI students at Al SMAI -Maarif Singosari.To achieve this goal, this research was conducted using a type of quantitative research using experimental methods with nonequivalent control group design. The research instruments in the form of tests and questionnaires were then tested for validity and reliability using the SPSS program. To test the hypothesis using a sample test paired sample t-test. The results of this study indicate that in the control class there is an average pretest value of 79.51 while the posttest mean value is 85.84 which is still lower than the experimental class. In the experimental class the average pretest score was 86.65 while the posttest average value was 91.84 higher than the control class. The average posttest value of the experimental class> control class is 91.84> 85.84 which means that the experimental class student learning outcomes are higher than the control class. In the paired t-test sample test, the test results obtained were sig-2 tailed at 0,000 <0,05, it was concluded that the use of interactive learning media based on the kahoot application had an effect on the learning outcomes of class XI students at Singosari Malang SMAI Al-Maarif means that the use of application-based learning media is more effective.